THE ROLE OF TOURISM AMBASSADOR IN PROMOTING THE TOURISM OBJECT IN SIDRAP REGENCY - Hernita Herman; Sam Hermansyah; Buhari (ADISAM Publisher, 2025)
This study uses qualitative methods as its research methodology. This research was conducted to determine the effectiveness of tourism ambassadors in promoting tourist destinations in Sidrap Regency and to find out the inhibiting factors for tourism ambassadors in promoting tourist destinations in Sidrap Regency. Population in the This research Formerly That student The number of Tourism Ambassadors for Sidrap Regency who were studied were 4 people. That data collection method used in the this research Formerly A interview. Based on the results of the interviews above, the effectiveness of tourist ambassadors in promoting tourist destinations is still not fully effective and realized, there are still many promotional programs from tourism ambassadors that have not been implemented and as for the obstacles for tourist ambassadors in Sidrap, lack of support and facilities provided by related parties in charge tourism ambassadors, for example media facilities that do not support tourism promotion.